Otonomi Daerah Peluang dan Problematikanya dalam Pembaruan Birokrasi Daerah - Susanto, Ely (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2002)
There are two contradictory results as the impact of the implementation of the outonomy policy to the good governance